2014
DOI: 10.1038/srep05129
|View full text |Cite
|
Sign up to set email alerts
|

Zeptomole Detection of C-Reactive Protein in Serum by a Nanoparticle Amplified Surface Plasmon Resonance Imaging Aptasensor

Abstract: Diagnostic biomarkers (i.e. proteins) are often in low abundance in bodily fluids presenting many challenges for their detection. In order to extend the application of SPRi systems in detecting biomarkers at ultralow levels, we combine the advantage of aptamer technology with nanomaterials and microwave-assisted surface functionalization. By implementing a sandwich assay through the introduction of aptamer-modified quantum dots (QDs), it was possible to measure 7 zeptomole (at 5 fg/mL) of C-reactive protein (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(79 citation statements)
references
References 33 publications
0
79
0
Order By: Relevance
“…We were able to detect as low as 0.5 ng/mL of gelatin (Figure 7D and Figure S6). 42 The fact that there was almost no change in SPR signal in the common protein solutions but there was over a 100 nm shift in the gelatin solution attests to the NP’s high binding specificity for denatured collagen as well as the potential for sensing collagen denaturation.…”
Section: Resultsmentioning
confidence: 99%
“…We were able to detect as low as 0.5 ng/mL of gelatin (Figure 7D and Figure S6). 42 The fact that there was almost no change in SPR signal in the common protein solutions but there was over a 100 nm shift in the gelatin solution attests to the NP’s high binding specificity for denatured collagen as well as the potential for sensing collagen denaturation.…”
Section: Resultsmentioning
confidence: 99%
“…As we previously reported 16,17 , the signal enhancement imparted by the NanoEnhancers is attributed to a mass loading effect and the strong coupling that exists between NIR fluorophores and propagating surface plasmons for gold film nanostructures. Even though, Nano-SPRi adds an extra step to the procedure, this level of sensitivity can widen the applications of SPRi technology in various outlets.…”
Section: Discussionmentioning
confidence: 75%
“…If the concentration of target analyte falls below the SPRi system's limit of detection (<nM), one has to resort to amplifying the SPRi signal via the utilization of nanoparticles (Nano-SPRi). Such SPR-based amplification has been well documented in the literature [16][17][18][19] for various types of analyte and surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, several ultrasensitive SPR biosensors involving QD-conjugated biomolecules have been developed [74][75][76]. In 2014, Sandros' group introduced aptamermodified QDs into an SPRi biosensor and demonstrated a record-high sensitivity of zeptomole (10 −21 moles) detection capability for C-reactive protein [77]. The same group had then shown that such an ultrasensitive platform could operate in multiplexed detection for clinical biomarkers [78].…”
Section: Spr Sensing With Non-plasmonic Nanoparticlesmentioning
confidence: 99%